The growth performance of Mucuna Bracteata, Puerariajavanica and Centrosema Pubescens on linau soil series / Mohd Alhafiz Mamat - Mamat, Mohd Alhafiz (Faculty of Plantation and Agrotechnology, 2015)
Legume cover crop (LCC) is an important plant that usually planted in oil palm and rubber estates for ground coverage and improved soil condition. Nowadays, the LCC that suitable to be planted on acidic soil are really needed to agricultural sector specially oil palm caused of that three leguminous crops, i.e. Mucuna bracteata, Pueraria javanica and Centrosema pubescens were evaluated on acid sulfate soils (linau series) as growth performance. The growth performance in number of leaves, number of nodes, fresh weight and dry weight of this crop was investigated and recorded. Mean for fresh biomass productions when harvested at week 12 were 25.63, 15.3 and 10.52 g/plant for Mbracteata, Pjavanica and C.pubescens respectively. The corresponding dry weights were 7.833, 5.237 and 4.702 g/plant. This study was conducted in the greenhouse of Universiti Teknologi MARA, Jasin, Malacca based on a completely randomized design (CRD). The result indicated that were no significant different in number of leaves, number of nodes, fresh and dry weight of leguminous crops on acid sulfate soil.